Evolution of Chinese lending to Sri Lanka since the mid-2000s: Separating myth from reality - Umesh Moramudali; Thilina Panduwawala (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2022)
China is Sri Lanka's largest bilateral creditor and has a significant role to play within the sovereign debt restructuring process that the crisis- stricken island nation is currently going through. This working paper provides a deep dive into China's lending to Sri Lanka over the last two decades and situates China within the overall changes in Sri Lanka's public external debt profile through its middle-income transition. Chinese lending to Sri Lanka has evolved through five distinct phases since 2000, expanding from bilateral lending to export credit and eventually balance of payments support through China Development Bank term loans since 2018 which became an alternative to raising eurobonds. The fifth phase is focused on Sri Lanka's historic sovereign default, and debt restructuring negotiations, which could define not only the future of Chinese lending to Sri Lanka but also to other BRI countries going through debt distress, including those in Africa. The ongoing debt restructuring process is not the first time Sri Lanka's government has asked for a loan restructuring from China Eximbank. In 2014, the then government proposed to restructure all Chinese loans obtained for the Hambantota Port project and create a joint venture with two Chinese SOEs to further develop the port terminals. While an election ended the earlier negotiations, the 99-year lease of the port in 2017 was a measure to address severe balance of payments issues, which the earlier plan had not tackled. The lease proceeds helped improve foreign currency reserves and there was no debt-to-equity swap nor an asset seizure, contrary to popular narrative. We found no deliberately 'hidden debt' in China's lending to Sri Lanka's public sector. Publicly available data from a number of Sri Lanka's public institutions provided full visibility for the US 7.4 billion in Chinese debt outstanding at end-2021. Chinese lending was then 19.6 percent of public external debt, much higher than the often-quoted 10-15 percent figures. A significant portion of Chinese debt has been recorded under state-owned enterprises, not the central government, but all of the Chinese debt was reported to the World Bank's International Debt Statistics. The nuances involved in ensuring full visibility of this debt show that public discourse, whether driven by media or academia, needs to take into account the complexities involved in how public debt is classified and reported in a country. At the same time, governments should ensure that public debt reporting is as simple, clear, and widely available as possible to facilitate open conversation.
Keywords: 330